Nest : a thriller - Goodkind, Terry (Skyhorse Publishing, 2016)
When a murder investigation reveals family secrets and exposes her to a shadowy network of evil, Kate accepts a mysterious author's offer to find answers, but time is running short as a force of super-predator killers is hot on their trail.